Aplikasi Kede Desa (KEDES) Untuk Digitalisasi UMKM Desa Klambir Lima Kebun - Jodi Hendrawan; Ika Devi Perwitasari; Daud Arifin (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
The process of running the MSME for the Klambir Lima Kebun village community is carried out conventionally, namely by word of mouth promotion, using banners, billboards and the business management and sales process is carried out manually which is recorded in the book. The methods used by the community experienced many problems and reduced service quality and led to management of sales reports. This will certainly require a solution so that it can improve the community's economy and the MSME community management process becomes better in a systematic manner. The digital Kede Desa (Kedes) system can be built with a responsive web-based system with the aim of being able to overcome the problems of MSME entrepreneurs becoming digital users and can implement it properly. The development cycle using the SDLC (Systems development life cycle) method is used to build a Kede Desa system so that it runs as expected and uses UML as a tool for documenting and making specifications on the system.